Internationalisation of contemporary Muslim higher education and ummatic development: a case study of the International Islamic University Malaysia - Hashim, Rosnani (IIUM Press, 2015)
The pressure for higher education to internationalise is very strong. Internationalisation is defined as the process of integrating international dimensions into teaching, learning, research and service. Internationalisation means major changes in five dimensions－faculty involvement in international activities, an internationalized curriculum, study abroad, international students and scholars, and college leadership. The most important change is in students and faculty compositions, the internationalised curriculum outlook, the requirement of a second language which in most cases is English, and the desire to be ranked in world ranking as a demonstration of quality. These changes may have many repercussions to a society social structure such as an encounter with cultural diversity, the education for fulfilling the needs of the international markets and the dominance of the English language. With the limited opportunity for English, it might creates a cleavage in society or marginalise the local national language. The attempts to be ranked could lead to frustration because of the nature of the ranking system itself. But from another perspective, it will enhance the formation of the global village having a common language for discourse. In this Chapter Rosnani analyses the impact of internationalisation of higher education through an examination of the practice of the International Islamic University Malaysia (IIUM). It attempts to find out whether IIUM has benefited from the policy of internationalisation.